My friend Anne Frank - Pick-Goslar, Hannah 1928-2022; Kraft, Dina (Rider, 2023)
"Firsthand account of a Holocaust survivor who knew Anne Frank"--
Keywords: Frank, Anne -- 1929-1945; Pick-Goslar, Hannah -- 1928-2022; Pick-Goslar, Hannah / Childhood and youth; Frank, Anne / 1929-1945 / Friends and associates; Jews / Netherlands / Amsterdam / Biography; Holocaust, Jewish (1939-1945) / Netherlands / Amsterdam / Biography; Amsterdam (Netherlands) / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; HISTORY / Europe / Eastern; HISTORY / Modern / 20th Century / Holocaust; BIOGRAPHY & AUTOBIOGRAPHY / Women; Frank, Anne / 1929-1945; Pick-Goslar, Hannah; Childhood and youth of a person; Friendship; Jews; Netherlands / Amsterdam; Jews / Biography; Holocaust, 1933-1945 / Biography; 1939-1945; Autobiographies; Biographies; Biografie